Faster Recovery of Internal Ophthalmoplegia than External Ophthalmoplegia in a Miller Fisher Variant of Guillain-Barre Syndrome - Golla Abhinav; Jorge Gamez; Michael C. Yang; Tetyana Vaysman; Michelle von Gunten; Antonio Liu (Case Reports in Ophthalmological Medicine)
We present a case of classic Miller Fisher Syndrome (MFS) variant of Guillain-Barre Syndrome (GBS) with detailed description in the difference between the internal and external ophthalmoplegia. They are different in their onset, duration, and recovery.